Optimizing the Analysis of Polycyclic Aromatic Hydrocarbons in Tea Samples - Thi Quynh, Nguyen; Thi Mai, Nguyen; Thi Lan Anh, Phan; Hong Anh, Duong; Thuy Ngoc, Nguyen; Hung Viet, Pham (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2, 2019)
Abstract: The optimization of sample preparation and gas chromatography - mass spectrometry (GC/MS)analysis was carried out to determine 15 polycyclic aromatic hydrocarbon compounds (PAHs) in tea. The method detection limit (MDL) for individual PAH in tea was in the range of 0.07 - 0.16 µg/kg; the recovery efficiency of the whole analytical procedure was from 53 to 132 % with good repeatability (RSD from 1.1 to 7.3 %). The application of the procedure to the analysis of Vietnamese green tea samplesresulted in the total content of PAHs in the range of 38.1 to 123 µg/kg. Compared with the European Commission's Regulation on the maximum allowed content of benzo(a)pyrene and the PAH4 group in dry herbs, all of the analyzed green tea samples have toxic PAH content at lower level than permitted. Keywords: PAHs, tea, GC/MS. References : [1] A. T. Lawal, Polycyclic aromatic hydrocarbons. A review, Cogent Environ. Sci. 3 (2017) 1-89 . https://doi.org/10.1080/23311843.2017.1339841 [2] P. Li, R. Xue, Y. Wang, R. Zhang, G. Zhang, Influence of anthropogenic activities on PAHs in sediments in a significant gulf of low-latitude developing regions, the Beibu Gulf, South China Sea: Distribution, sources, inventory and probability risk, Mar. Pollut. Bull. 90 (2015) 218-226. https://doi.org/10.1016/j.marpolbul.2014.10.048 [3] F. S. Ehrenhauser, PAH and IUPAC Nomenclature, Polycycl. Aromat. Compd. 35 (2015) 161–176. https://doi.org/10.1080/10406638.2014.918551 [4] Z. Zelinkova, T. Wenzl, The Occurrence of 16 EPA PAHs in Food – A Review, Polycycl. Aromat. Compd. 35 (2015) 248–284. https://doi.org/10.1080/10406638.2014.918550 [5] M. Mari, R. M. Harrison, M. Schuhmacher, J. L. Domingo, S. Pongpiachan, Inferences over the sources and processes affecting polycyclic aromatic hydrocarbons in the atmosphere derived from measured data, Sci. Total Environ. 408 (2010) 2387–2393. https://doi.org/10.1016/j. scitotenv.2010.01.054 [6] L. Singh and T. Agarwal, PAHs in Indian diet: Assessing the cancer risk, Chemosphere 202 (2018) 366–376. https://doi.org/10.1016/j. chemosphere. 2018.03.100 [7] K. H. Kim, S. A. Jahan, E. Kabir, R. J. C. Brown, A review of airborne polycyclic aromatic hydrocarbons (PAHs) and their human health effects, Environ. Int. 60 (2013) 71–80. https://doi.org/10.1016/j.envint.2013.07.019 [8] G. M. Guatemala-Morales, E. A. Beltrán-Medina, M. A. Murillo-Tovar, P. Ruiz-Palomino, R. I. Corona-González, E. Arriola-Guevara, Validation of analytical conditions for determination of polycyclic aromatic hydrocarbons in roasted coffee by gas chromatography-mass spectrometry, Food Chem. 197 (2016) 747–753. https://doi.org/10.1016/j. foodchem.2015.10.135 [9] A. Paris, J. Ledauphin, P. Poinot, J. L. Gaillard, Polycyclic aromatic hydrocarbons in fruits and vegetables: Origin, analysis, and occurrence, Environ. Pollut. 234 (2018) 96–106. https://doi.org/10.1016/j.envpol.2017.11.028 [10] Y. Li, C. Wang, X. Zou, Z. Feng, Y. Yao, T. Wang, C. Zhang, Occurrence of polycyclic aromatic hydrocarbons (PAHs) in coral reef fish from the South China Sea, Mar. Pollut. Bull. 139 (2019) 339–345. https://doi.org/10.1016/j. marpolbul.2019.01.001 [11] M. Rose, J. Holland, A. Dowding, S.R. Petch, S. White, A. Fernandes, D. Mortimer, Investigation into the Formation of PAHs in Foods Prepared in the Home to Determine the Effects of Frying, Grilling, Barbecuing, Toasting and Roasting, Food and Chemical Toxicology 78 (2015) 1–9. https://doi.org/10.1016/j.fct.2014.12.018 [12] Heidelore Fiedler, C.K. Cheung, M.H. Wong, PCDD/PCDF, chlorinated pesticides and PAH in Chinese teas, Chemosphere 46 (2002) 1429-1433. https://doi.org/10.1016/S0045-6535(01) 00264-8 [13] I. C. T. Nisbet, P. K. LaGoy, Toxic equivalency factors (TEFs) for polycyclic aromatic hydrocarbons (PAHs)” Regul. Toxicol. Pharmacol 16 (1992) 290–300. https://www. ncbi.nlm.nih.gov/pmc/articles/PMC2898023 [14] European Commission, Commission Regulation (EU) 2015/1933 of 27 October 2015 amending Regulation (EC) No 1881/2006 as regards maximum levels for polycyclic aromatic hydrocarbons in cocoa fibre, banana chips, food supplements, dried herbs and dried spices, Official Journal of the European Union Legistation L. 282 (2015) 11–13. https://eur-lex.europa.eu/legal-content/EN/TXT/PDF/?uri= CELEX:32015R1933&rid=1 [15] M. Da Silva Pinto, Tea: A new perspective on health benefits, Food Res. Int. 53 (2013) 558–567. https://doi.org/10.1016/j.foodres.2013.01.038 [16] T. M. Rains, S. Agarwal, K. C. Maki, Antiobesity effects of green tea catechins: A mechanistic review, J. Nutr. Biochem. 22 (2011) 1–7. https://doi.org/10.1016/j.jnutbio.2010.06.006 [17] Đỗ Ngọc Quý, Cây Chè: Sản Xuất, Chế Biến, Tiêu Thụ, NXB Nghệ An, 2003. [18] Bộ Khoa học và Công nghệ, 2013, Tiêu chuẩn quốc gia TCVN 9740:2013: Chè xanh- định nghĩa và các yêu cầu cơ bản, http://tieuchuan.vsqi.gov. vn/tieuchuan/view?sohieu=TCVN+9740%3A2013 [19] D. Lin, L. Zhu, W. He, Y. Tu, Tea plant uptake and translocation of polycyclic aromatic hydrocarbons from water and around air, J. Agric. Food Chem. 54 (2006) 3658–3662. https://doi.org/10.1038/s41598-017-12437-w [20] F. Rolle, F. Pennecchi, S. Perini, M. Sega, Metrological traceability of Polycyclic Aromatic Hydrocarbons (PAHs) measurements in green tea and mate, Meas. J. Int. Meas. Confed. 98 (2017) 290–299. https://doi.org/10.1016/j.measurement. 2016.03.009 [21] Bộ Khoa học và Công nghệ, 2013, Tiêu chuẩn quốc gia TCVN 9318-2012: Chất lượng đất – xác định hydrocacbon thơm đa vòng (PAH) phương pháp sắc ký khí dùng detector khối phổ (GC-MS), http://tieuchuan.vsqi.gov.vn/tieuchuan/view?sohieu=TCVN+9318%3A2012 [22] European Commission, Commission Regulation (EU) No 836/2011 of 19 August 2011 amending Regulation (EC) No 333/2007 laying down the methods of sampling and analysis for the official control of the levels of lead, cadmium, mercury, inorganic tin, 3-MCPD and benzo (a)pyrene in foodstuffs, Official Journal of the European Union Legistation L. 54 (2011) 9–16. https://eur-lex.europa.eu/legal-content/EN/TXT/?uri= CELEX:02007R0333-20120901 [23] Phòng thí nghiệm trọng điểm Công nghệ phân tích phục vụ kiểm định môi trường và an toàn thực phẩm, Báo cáo Nhiệm vụ thường xuyên của Phòng thí nghiệm trọng điểm Đại học Quốc gia Hà Nội (mã số: NVTX.2018.03), 2018. [24] V. A. Garcia Londono, C. M. Reynoso, S. L. Resnik, Polycyclic aromatic hydrocarbons (PAHs) survey on tea (Camellia sinensis) commercialized in Argentina, Food Control. 50 (2015) 31–37. https://doi.org/10.1016/j.foodcont. 2014.07.036 [25] A. Zachara, D. Gałkowska, L. Juszczak, Contamination of tea and tea infusion with polycyclic aromatic hydrocarbons, Int. J. Environ. Res. Public Health. 15 (2018) 45. https://doi.org/10.3390/ijerph15010045 [26] M. Tomaniova, K. Kalachova, L. Drabova, V. Kocourek, J. Hajslova, J. Pulkrabova, Rapid determination of polycyclic aromatic hydrocarbons (PAHs) in tea using two-dimensional gas chromatography coupled with time of flight mass spectrometry, Talanta. 100 (2012) 207–216. https://doi.org/10.1016/j. talanta.2012.07.081 [27] K. Ziegenhals, W. Jira, K. Speer, Polycyclic aromatic hydrocarbons (PAH) in various types of tea, Eur. Food Res. Technol. 228 (2008) 83–91. https://doi.org/10.1007/s00217-008-0909-8